Religious Moderation in the Qur'an and Hadith: Theological Foundations and Implications for Contemporary Life - Yansah, Savri; Zubaedi; Toha Andiko; Moch. Iqbal (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Religious moderation is an important principle in Islamic teachings which is reflected in the teachings of the Qur'an and hadith. Islam was revealed as a religion that brings grace, balance, and justice to the entire world. This article aims to examine the foundations of religious moderation from the perspective of the Qur'an and hadith and its relevance in the context of multicultural and multireligious society. With a thematic approach and normative analysis, this article highlights the importance of tawassuth (middle), tasamuh (tolerance), and i'tidal (fair) attitudes in strengthening social cohesion and maintaining world peace. This research seeks to reveal religious moderation in the Qur'an and the hadith